Diagnostic Challenges of Eosinophilic Granulomatosis with Polyangiitis: A Case Report (London Journal of Medical and Health Research, 2026)
Eosinophilic granulomatosis with polyangiitis (EGPA) is a systemic vasculitis that predominantly affects small blood vessels and occurs in patients with asthma and tissue eosinophilia. The form associated with anti-neutrophil cytoplasmic antibodies (ANCA) is rarer. This case report presents a patient with late-onset asthma who initially presented with skin lesions (purpura), progressing to acute kidney injury, and subsequently diagnosed with glomerulonephritis. The difficulty and complexity of the clinical diagnosis and the importance of initiating appropriate and early therapy to minimize damage to target organs, improve prognosis, and avoid adverse effects motivated the presentation of this case and its literature review.
Keywords: Churg-Strauss syndrome; eosinophilia; eosinophilic granulomatosis with polyangiitis; vasculitis